Effect of Homogenization Process on the Production of Arthrospira platensis Carotenoid Nanocapsules Encapsulated with Arabic Gum and Whey Protein Concentrate - Khusnul Alfionita; Siti Ari Budhiyanti; Nurfitri Ekantari (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchThe homogenization process affected the particle size reductionThe homogenization process using both High Speed Homogenizer and Ultrasound had a smaller particle size and the highest efficiency in encapsulation AbstractArthrospira platensis contains a high concentration of carotenoids mainly 80 % β-carotene. The use of β-carotene in functional food and nutritional supplements was constrained by its lack of chemical and physical stability. Therefore, efforts were needed to protect carotenoids from damage by using an encapsulation system. The emulsion preparation before the encapsulation process had an influence on the stability of the oil-in-water emulsion. Various methods were used to prepare emulsions, such as high shear homogenizers (HSH) and ultrasound (US) treatment. The homogenization step was critical because it influenced the chemical stability of any encapsulated compounds. The purpose of this work was to generate nanocapsules of β-carotene with minimum carotenoid degradation, high efficiency of encapsulation, and small particle size, with variation in the homogenization process. This study consisted of 5 treatments, including the homogenization processes used HSH 24.000 rpm for 90 s ; HSH 24.000 rpm for 60 s, amplitude 55 % for 120 s ; amplitude 94 % for 138 s ;  amplitude 55 % for 138 s ;  and  amplitude 55 % for 120 s . Each parameter was analysed by ANOVA followed by Tukey pairwise comparisons with 95% confidence level and p<0.05. The particle size was influenced by the emulsification process, such as homogenization treatment, homogenization time, amplitude, and time of sonication. The sample that was homogenized using both HSH and US had a smaller particle size and the highest efficiency in encapsulation than others. The combination of homogenization process could decrease particle size.